1988
DOI: 10.1021/bi00420a029
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a genomic and cDNA clone coding for the thioesterase domain and 3' noncoding region of the chicken liver fatty acid synthase gene

Abstract: The fatty acid synthase (FAS) of animal tissue is a dimer of two identical subunits, each with a Mr of 260,000. The subunit is a single multifunctional protein having seven catalytic activities and a site for binding of the prosthetic group 4'-phosphopantetheine. The mRNA coding for the subunit has an estimated size of 10-16 kb, which is about twice the number of nucleotides needed to code for the estimated 2300 amino acids. We have isolated a positive clone, lambda CFAS, containing FAS gene sequences by scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Comparison of the amino acid sequence of rape thioesterase with long chain thioesterases from animal [2,11,17] or yeast [3] systems reveals no significant homologies, in agreement with observations made with the safflower thioesterase [ 12]. The GXSXG serine active site consensus sequence [ 1 ] present in animal thioesterases and in other acyl transferases and lipases is not present in the rape thioesterase sequence, again in agreement with findings with the safflower enzyme [12].…”
Section: H E L Q I T L D Y R R E C Q D D I V D S L T Se D I S K L G Tsupporting
confidence: 81%
“…Comparison of the amino acid sequence of rape thioesterase with long chain thioesterases from animal [2,11,17] or yeast [3] systems reveals no significant homologies, in agreement with observations made with the safflower thioesterase [ 12]. The GXSXG serine active site consensus sequence [ 1 ] present in animal thioesterases and in other acyl transferases and lipases is not present in the rape thioesterase sequence, again in agreement with findings with the safflower enzyme [12].…”
Section: H E L Q I T L D Y R R E C Q D D I V D S L T Se D I S K L G Tsupporting
confidence: 81%
“…Several reports indicated that the mutations in FASN gene were associated with (Bhuiyan et al, 2009;Lee et al, 2010;Zhang et al, 2008). Also, the polymorphisms in chicken FASN gene have been reported by Marrube et al (2004) and this gene is located on chromosome 18 and had three TE domains in exons 40, 41 and 42 (Kasturi et al, 1988).…”
Section: Introductionmentioning
confidence: 90%
“…In case of FASN gene in chicken liver, Kasturi et al (1988) observed that TE domain was located in exon 40-42 that might be also responsible for fatty acid analysis in chicken. In addition, the lack of association might also be highlighted by the sample size that has often failed to validate the analysis.…”
Section: Fasn and Scd Gene Effects To Fa Compositionmentioning
confidence: 99%
“…Isolation and Characterization of Genomic Clones-The human liver genomic library was screened at a density of 3,000 plaques/90-mm plate by using a [␣-32 P]dCTP-labeled 485-bp human FAS cDNA fragment, Try3-27 (25), as a probe as described previously (26). Approximately 2 ϫ 10 6 plaques were screened.…”
Section: Methodsmentioning
confidence: 99%